Accounting policy and regulation of the civil society organizations activities (Economics and region, 2024)
The relevance of the topic is determined by the need of Ukrainian society for reliable information about the civil society organizations activities. The concept of accounting in civil society organizations involves taking into account their organizational and legal features and differences in the purposes of activity compared to business entities that provide for the implementation of profitable activities. For civil and charitable organizations, the purpose of creation, the refusal to receive profit, as well as the payment of any reward or compensation, compliance with the ban on the distribution of property and income between participants, and ensuring the targeted nature of the financing of activities are important. The characteristics and peculiarities of the activities of civil sector organizations determine the accounting policy and affect the completeness and reliability of financial and other information. The author analyzed the differences in the functioning of civil and charitable organizations in Ukraine. The definition of civil society in UN, World Bank, and EU documents is indicated, which are different from the national legislation oriented on the organizational form of activity. The current state and development trends of the accounting system of the activities of civil society organizations in Ukraine are analyzed. A comparison of accounting policy elements according to national and International Accounting Standards was made. The main scientific views on the accounting policy of economic entities are summarized. It is indicated about the possibilities of application by civil society organizations of simplified accounting and reporting rules: a simplified chart of accounts and financial statements. The importance of the choice of the accounting and reporting system by the civil society organization in the administrative documents on the accounting policy and organization of accounting is emphasized. The article substantiates and provides practical recommendations for improving the accounting policy of civil society organizations. The author suggests that when forming the NGO accounting policy of assets, liabilities, capital, income and expenses, the provision of public (social) services should be noted as a future economic benefit. In view of the modern challenges of the time, in particular those related to the state of war (targeted financing, grants, government assistance, aid, monetary funds, currency operations, customers, etc.), the issues of accounting, reporting and taxation of civil society organizations require further research.
Keywords: civil society; civil society organisations; charity organisations; NGO; Nonprofit Governance; Nonprofit Organizations; accounting policy; accounting; Financial Statements